Managing intra-EU mobility-do WHO principles of ethical recruitment have relevance? - Réka Kovács; Edmond Girasek; Eszter Kovács; Zoltán Aszalós; Edit Eke; Károly Ragány; Zoltán Cserháti; Miklós Szócska (BMC, 2017)
Abstract Background The WHO Global Code of Practice on the International Recruitment of Health Personnel provides for guidance in health workforce management and cooperation in the international context. This article aims to examine whether the principles of the voluntary WHO Global Code of Practice can be applied to trigger health policy decisions within the EU zone of free movement of persons. Methods In the framework of the Joint Action on European Health Workforce Planning and Forecasting project (Grant Agreement: JA EUHWF 20122201 (see healthworkforce.eu)), focus group discussions were organised with over 30 experts representing ministries, universities and professional and international organisations. Ideas were collected about the applicability of the principles and with the aim to find EU law compatible, relevant solutions using a qualitative approach based on a standardised, semi-structured interview guide and pre-defined statements. Results Based on implementation practices summarised, focus group experts concluded that positive effects of adhering to the Code can be identified and useful ideas-compatible with EU law-exist to manage intra-EU mobility. The most relevant areas for intervention include bilateral cooperations, better use of EU financial resources, improved retention and integration policies and better data flow and monitoring. Improving retention is of key importance; however, ethical considerations should also apply within the EU. Compensation of source countries can be a solution to further elaborate on when developing EU financial mechanisms. Intra-EU circular mobility might be feasible and made more transparent if directed by tailor-made, institutional-level bilateral cooperations adjusted to different groups and profiles of health professionals. Integration policies should be improved as discrimination still exists when offering jobs despite the legal environment facilitating the recognition of professional qualifications. A system of feedback on registration/licencing data should be promoted providing for more evidence on intra-EU mobility and support its management. Conclusions Workforce planning in EU Member States can be supported, and more equitable distribution of the workforce can be provided by building policy decisions on the principles of the WHO Code. Political commitment has to be strengthened in EU countries to adopt implementation solutions for intra-EU problems. Long-term benefits of respecting global principles of the Code should be better demonstrated in order to incentivise all parties to follow such long-term objectives.